ANALISIS PENGARUH REWARD, MOTIVASI, DAN KEPUASAN KERJA TERHADAP TURNOVER INTENTION PADA PT. INDO NINIKI - Bill Juvendy; Yossi Hendriati (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2020)
PT. Indo Niniki is one freight forwarder company in Batam. PT. Indo Niniki currently experiencing increasing employee turnover over the last three years. As we know, the amount of turnover that occurs in the company will give a negative effect on the sustainability of the company and weaken the company’s position in competing with its competitors in the market of logistics industry. The purpose of this study was to find out what is the reason that cause a high turnover intention in this company. Based on the interview with the Director of PT. Indo Niniki, the reason is the employee was not satisfied and feel bored with their job, causing employees are not motivated to be in the company. The method used is the method of associative research and direct observation in the company. Data collectedby interviews and questionnaires to the company’s employees. A questionnaire was distributed to all of the employees of PT. Indo Niniki to know their motivation and job satisfaction as well as their opinion on the reward that provided by the company. Data analysis techniques using simple regression and multiple regression formula Y = a + b1x1 + b2X2 + b3X3 by the use of SPSS software. The results and information of this research that obtained from the questionnaires will be the result of a hypothetical answer which will provide useful advice for the company